2013
DOI: 10.1371/journal.pone.0084328
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric and Micronutrient Status of School-Children in an Urban West Africa Setting: A Cross-Sectional Study in Dakar (Senegal)

Abstract: BackgroundUrban areas in West Africa are not immune to undernutrition with recent urbanization and high food prices being important factors. School children often have a poor nutritional status, potentially affecting their health and schooling performance. Yet, generally school children do not benefit from nutrition programs. The objective of the study was to assess the anthropometric and micronutrient status of children from state schools in the Dakar area.MethodsSchool children (n = 604) aged from 5 to 17 y … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 27 publications
4
29
0
1
Order By: Relevance
“…Even if energy intake increased with age, insufficient fiber, protein and micronutrient intake and inadequate contribution of macronutrients to total energy intake were higher among adolescents compared to children <10 years, which suggests poorer nutrition in adolescents, where mean height for age was lower in the present study [9]. A research conducted in Cameroonian urban adolescents also reported a high prevalence of insufficient contribution of proteins to energy intake [21].…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…Even if energy intake increased with age, insufficient fiber, protein and micronutrient intake and inadequate contribution of macronutrients to total energy intake were higher among adolescents compared to children <10 years, which suggests poorer nutrition in adolescents, where mean height for age was lower in the present study [9]. A research conducted in Cameroonian urban adolescents also reported a high prevalence of insufficient contribution of proteins to energy intake [21].…”
Section: Discussionmentioning
confidence: 57%
“…Here, 600 school children were randomly selected through a two-stage random cluster sampling of children attending state primary schools in the Dakar area (30 schools × 20 children). Details of study design and sampling are provided elsewhere [9]. Adolescents were defined as equal or above 10 years [10].…”
Section: Participants and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…26 Persentase stunting 4,9%, 18,4% kurus dan 5,6% status gizi sangat kurus ditemukan pada anak sekolah dasar di Dakar, Senegal berdasarkan pengukuran pada 604 siswa sekolah dasar, pengukuran zat gizi mikro menunjukkan 35,9% defesiensi vitamin A marginal dan 25,9% defesiensi seng. 27 Hasil penelitian di Visakhapatnam, India juga mendapatkan masih tingginya persentase masalah gizi kurang pada anak usia sekolah yakni 60%.…”
Section: Copyright © 2018; Jurnal Gizi Indonesia (The Indonesian Jourunclassified